Factors Influencing Adoption of Hospital-Acquired Pressure Ulcer Prevention Programs in US Academic Medical Centers. Issue 4 (July 2015) - Padula, William V.; Valuck, Robert J.; Makic, Mary Beth F.; Wald, Heidi L.
Abstract : PURPOSE: Recent data show a decrease in hospital-acquired pressure ulcers (PUs) throughout US hospitals; these changes may be associated with increased success in implementing evidence-based practices for PU prevention. The purpose of this study was to identify wound care nurse perceptions of the primary factors that influenced the overall reduction of PUs. DESIGN: Cross-sectional descriptive survey. SUBJECTS AND SETTING: Surveys were sent to wound care nurses at 98 University HealthSystem Consortium (UHC) hospitals. The UHC consists of more than 120 academic medical centers and affiliated facilities across the United States. Responses solicited from this survey represented a geographically diverse set of hospitals from less than 200 beds to more than 1000 beds. INSTRUMENT: The survey questionnaire used a framework of 7 internal and 5 external influential factors for implementing evidence-based practices for PU prevention. Internal influential factors queried included availability of nurse specialists, high nursing job turnover, high PU rates, and prevention campaigns. External influential factors included data sharing, Medicare nonpayment policy, and applications for Magnet recognition. METHODS: Hospital-acquired PU prevention experts at UHC hospitals were contacted through the Wound, Ostomy and Continence Nurses Society membership directory to complete the questionnaire. Consenting participants were e-mailed a disclosure and online questionnaire; they were also sent monthly reminders until they either responded to the survey or declined participation. RESULTS: Fifty-five respondents (59% response rate) indicated several internal factors that influenced evidence-based practice: hospital prevention campaigns; the availability of nursing specialists; and the level of preventive knowledge among hospital staff. External influential factors included financial concerns; application for Magnet recognition; data sharing among peer institutions; and regulatory issues. CONCLUSIONS: These findings suggest that the Centers for Medicare & Medicaid Services nonpayment policy influenced a large majority of hospital's changes in practice. The availability of nursing specialists for wound consult influenced hospitals internally. These factors are informative of the impact policy has on changes in hospital prioritization of adopting evidence-based practices for PU prevention.